2017
DOI: 10.1136/jim-2016-000244
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Evaluation and Expression of the Pluripotent Mesenchymal Stem Cell-Like Markers Cd105 and Cd44 in the Synovial Membrane of Patients with Primary versus Secondary Hip Osteoarthritis

Abstract: To present the morphological changes of classic primary versus rapidly progressive and secondary hip osteoarthritis (HO) and to examine the expression of two pluripotent mesenchymal stem cell-like markers in the synovial membrane. A prospective observational study was conducted in 57 consecutive cases of radiologically confirmed HO in which total hip arthroplasty was performed. Based on the radiological and clinicopathological features, the cases were divided into three categories: classic primary HO (group A;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…It has been reported that MSCs play an important role in the pathogenesis of osteoarthritis, which have been identified in normal structures and diseased tissues [56,57], but there is still little research on the role of SM-MSCs in the progression of HO disease. Turdean et al [55] found CD105 and CD44 double-positive MSCs were present both in the lining and sub-lining layer of the hip joint, and it has been confirmed that the classic primary HO is mainly characterized by inflammatory infiltration around the blood vessel and simple synovium cell hyperplasia, while the rapidly destructive HO manifested as papillary synovial hyperplasia and the formation of germinal center in the sub-lining layer. The study also confirmed that the severity of rapidly destructive HO disease progression may be related to large-scale immune mobilization mediated by CD44/CD105 double-positive SM-MSCs.…”
Section: Study Of Sm-mscs In Osteoarthritis (Oa)mentioning
confidence: 88%
See 1 more Smart Citation
“…It has been reported that MSCs play an important role in the pathogenesis of osteoarthritis, which have been identified in normal structures and diseased tissues [56,57], but there is still little research on the role of SM-MSCs in the progression of HO disease. Turdean et al [55] found CD105 and CD44 double-positive MSCs were present both in the lining and sub-lining layer of the hip joint, and it has been confirmed that the classic primary HO is mainly characterized by inflammatory infiltration around the blood vessel and simple synovium cell hyperplasia, while the rapidly destructive HO manifested as papillary synovial hyperplasia and the formation of germinal center in the sub-lining layer. The study also confirmed that the severity of rapidly destructive HO disease progression may be related to large-scale immune mobilization mediated by CD44/CD105 double-positive SM-MSCs.…”
Section: Study Of Sm-mscs In Osteoarthritis (Oa)mentioning
confidence: 88%
“…Hip osteoarthritis (HO) is the most common joint disease among the old people. About 50% of the over 65-year-old people are affected, and the incidence of females is higher [55]. HO is the result of progressive degeneration of articular cartilage.…”
Section: Study Of Sm-mscs In Osteoarthritis (Oa)mentioning
confidence: 99%
“…One study showed that the number of SF-MSCs increased with cartilage degeneration and the severity of osteoarthritic disease compared to healthy controls [19].During OA progression, CD44 expression gradually increases [33]. The development of hip OA may be linked to widespread immunological mobilization driven by SM-MSCs that are CD44/CD105 double positive [34] and articular cartilage CD44 expression levels and SF-MSC CD44 expression levels correlated with OA joint severity [35]. SM-MSCs are crucial for the early preservation of bone joints.…”
Section: Role Of Sm-mscs and Sf-mscs In Arthritismentioning
confidence: 99%
“…Synovial tissue was studied in several joints, including 17 studies on the knee [68,[92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107], 5 studies on hip [108][109][110][111][112], 6 studies used a combination of knee and hip synovium [113][114][115][116][117][118], 2 studies on TMJ [119,120], and 10 studies did not report the joint site [121][122][123][124][125][126][127][128][129][130]. The ECM components that were most often studied in human synovium were collagens, fibronectins, and laminins.…”
Section: Synovium In Human Oamentioning
confidence: 99%